HONORARY FELLOW - R.S. SINGH - SINGH, R.S. (Indian Phytopathology, 2002)
Prof. R.S. Singh was born at village Gagaha in Gorakhpur district on 1st March, 1927. He did his matriculation in 1942 and was enrolled at the Government Agricultural College, Kanpur for his Post Graduation. In 1948 he obtained Masters Degree in plant pathology with distinction. He continued as a Research Assistant and became lecturer in plant pathology in 1951. He was awarded degree of Doctor of Philosophy by Agra University in 1956.